Role of potassium, magnesium, sulphur and copper nutrients on groundnut late leaf spot disease dynamics: ROLE OF POTASSIUM, MAGNESIUM, SULPHUR AND COPPER ON GROUNDNUT LATE LEAF SPOT DISEASE - D R S VINEELA; A K PATIBANDA; V PRASANNAKUMARI; B SREEKANTH; S K NAFEEZ UMAR (Journal of Oilseeds Research, 2023)
Plant protection strategies need an effective alternative mode that reduces chemical load on environment and financial burden on farmers. Mineral nutrition, an integral part of crop production has long since proven to be a promising management strategy. Due to high specificity of host-pathogen-nutrient relationship, precise investigation has to be taken before recommendation. Among the various methods to screen infection frequency and disease tolerance with respect to applied treatments, components of resistance (incubation period, latent period, number of leaf spots, and lesion diameter) studied in hydroponically grown plants under greenhouse conditions are more appropriate than detached leaf assay as disease development of late leaf spot caused by the hemibiotroph., Phaeoisariopsis personata is more akin to the disease development under field conditions. Role of four nutrients i.e., Potassium, Magnesium, Sulphur and Copper deficient conditions as well as supplementation alone and in combination on groundnut late leaf spot disease incidence was compared with fungicidal check (Tebuconazole seed treatment) in terms of components of resistance and anti-oxidant enzyme activities using sand culture. Deficiency of nutrients showed higher disease incidence than control suggesting the role of nutrients in offering resistance to infection. Further it is revealed that CuSO4 and combination of four nutrients were effective in delaying incubation (11.67 days, 12.33days) and latent period (16.67 days, 17.00 days) while MgSO4 followed by combination of four nutrients were effective in reducing lesion number (17.65/leaf, 22.15/leaf) and diameter (0.20 and 0.27 mm) thus lowered AUDPC which showed similar antioxidant enzyme activity as fungicidal check. Nutrient supplementation though inferior to fungicidal check (14 days incubation period, 18.33 dayslatent period, 1.95 lesions/leaf with 0.22mm diameter), wassignificantlysuperior to control (10.33 daysincubation period, 13.67 days latent period, 70.15lesions/leaf with 0.33mm diameter). Hence, application of adequate amount of nutrients improves plants growth as well as resistance to LLS infection.